2006
DOI: 10.1074/jbc.m510527200
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone-related Protein Regulates Tumor-relevant Genes in Breast Cancer Cells

Abstract: The effect of endogenous parathyroid hormone-related protein (PTHrP) on gene expression in breast cancer cells was studied. We suppressed PTHrP expression in MDA-MB-231 cells by RNA interference and analyzed changes in gene expression by microarray analysis. More than 200 genes showed altered expression in response to a PTHrP-specific small interfering (si) RNA (siPTHrP). Cell cycle-regulating gene CDC2 and genes (CDC25B and Tome-1) that control CDC2 activity showed increased expression in the presence of siPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 85 publications
0
31
1
1
Order By: Relevance
“…3G-J). Recently, it is reported that PTHrP translocates into the nucleus and functions in an intracrine manner, which is associated with altered cell-cycle progression and protection from apoptosis [15][16][17]. We noted nuclear localization of PTHrP in addition to a cytoplasmic signal; however, PTHrP may not participate in apoptotic pathways in OSCC, since we found no cleaved Caspase-3, -9, or PARP in cells deficient in PTHrP (data not shown).…”
Section: Discussionmentioning
confidence: 42%
“…3G-J). Recently, it is reported that PTHrP translocates into the nucleus and functions in an intracrine manner, which is associated with altered cell-cycle progression and protection from apoptosis [15][16][17]. We noted nuclear localization of PTHrP in addition to a cytoplasmic signal; however, PTHrP may not participate in apoptotic pathways in OSCC, since we found no cleaved Caspase-3, -9, or PARP in cells deficient in PTHrP (data not shown).…”
Section: Discussionmentioning
confidence: 42%
“…However, several studies have suggested PTHrP expression in the tumor might act against its progression, and be associated with better prognosis during early stage (15,23), and non-invasive breast cancer (16). Experimental analyses have also suggested that PTHrP has little involvement in the initial stages of metastasis (24,25). These observations suggest that PTHrP expression plays a role in preventing breast cancer progression while the disease remains in situ.…”
Section: Discussionmentioning
confidence: 86%
“…Besides the PTHlike domain, which lies within the N-terminal, part of the PTHrP protein, PTHrP contains two other functional domains, the mid-region and C-terminal domains. Post-translational cleavage of the PTHrP protein allows these domains to function independently (14)(15)(16)(17). By activation of PTH1R, the N-terminal parathyroid hormone-like domain stimulates protein kinase A (PKA), C (PKC), and/or the calcium-dependent pathways, respectively (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Post-translational cleavage of the PTHrP protein allows these domains to function independently (14)(15)(16)(17). By activation of PTH1R, the N-terminal parathyroid hormone-like domain stimulates protein kinase A (PKA), C (PKC), and/or the calcium-dependent pathways, respectively (17)(18)(19)(20). The mid-region domain, containing a bipartite nuclear localization sequence at residues 88-91 and 102-106 and an importin ß-binding site at 66-94, can enter the nucleus and interfere with gene expression (17,(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation